Draft Five Year Plan 1978-83 State Capital Project Government of Madhya Pradesh - Planning Commission (Planning Commission, 1978)
The financial outlay during the Vth Five year plan was Rs. 1040 lakhs against which an expenditure of Rs. 1374 lakhs was actually incurred. An outlay of Rs. 2500 lakhs has been proposed for the VI th Five Year Plan.
Government of Madhya Pradesh, Planning, Economics and Statistics Department